FIQIH SIYASAH DUSTURIYAH ANALYSIS OF LIMITATIONS ON PROVISION OF SOCIAL AID FUNDS (STUDY OF MINISTER OF SOCIAL REGULATION NUMBER 1 OF 2019 CONCERNING DISTRIBUTION OF SOCIAL AID EXPENDITURES) - Rahmadani, Selvi; Emrizal, Emrizal; Putri, Dewi (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
The aim of this research is to find out and explain which categories of people receive social assistance and the forms of restrictions on providing social assistance from the state to the community. To answer the research focus in this study, researchers used normative legal research methods. The results of this research show that the categories of people who receive and the limitations on providing social assistance have been determined by regulations. Review of siyasah dusturiyah on the topic of siyasah tasriiyah studies which emphasizes the aspects of law and legislation in Islam which include making rules and regulations to regulate people's lives